2003
DOI: 10.1099/mic.0.26565-0
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic specificity of the rhamnosyltransferase gene of Mycobacterium avium serovar 2 as determined by allelic exchange mutagenesis

Abstract: In prior studies, through recombinant expression in Mycobacterium smegmatis, the rtfA gene of Mycobacterium avium was shown to encode a rhamnosyltransferase that catalyses the addition of rhamnose (Rha) to the 6-deoxytalose of serovar 2-specific glycopeptidolipid (GPL). Whether RtfA also catalyses the transfer of Rha to the alaninol of the lipopeptide core is unknown. An isogenic rtfA mutant of M. avium serovar 2 strain TMC724 was derived using a novel allelic exchange mutagenesis system utilizing a multicopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…rtfA functions to catalyze only the addition of Rha to 6-d-Tal (26), and which gene cluster transfers additional sugars to L-Rha elongated from 6-d-Tal is unclear. ORFs 1, 3, and 9 have high homology to the glycosyltransferases GtfA, Rv1516c, and Rv1518, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…rtfA functions to catalyze only the addition of Rha to 6-d-Tal (26), and which gene cluster transfers additional sugars to L-Rha elongated from 6-d-Tal is unclear. ORFs 1, 3, and 9 have high homology to the glycosyltransferases GtfA, Rv1516c, and Rv1518, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…PCR was used to isolate cosmid clones carrying the rhamnosyltransferase (rtfA) gene with primers rtfA-F (5Ј-TTTTGGAGCGACGAGTTCATC-3Ј) and rtfA-R (5Ј-GTGTAGTTGACCACGCCGAC-3Ј). rtfA encodes an enzyme responsible for the transfer of Rha to 6-d-Tal in OSE (11,26). The insert of cosmid clone 49 was sequenced using a BigDye Terminator, version 3.1, Cycle Sequencing Kit (Applied Biosystems, Foster City, CA) and an ABI Prism 310 gene analyzer (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact function of the genes potentially involved remains unknown, with one exception. It has been experimentally demonstrated that the rtfA gene encodes rhamnosyltransferase that catalyses the addition of rhamnose to 6-dTal (Eckstein et al, 1998;Maslow et al, 2003). Glycosylation performed by rhamnosyltransferase is assumed to be the first step in the conversion of the non-specific GPLs to serotype-specific GPLs.…”
Section: Introductionmentioning
confidence: 99%
“…Modification of the GPL structure might play an important role not only in antigenicity but also in host immune responses and bacterial physiology (18). Recently, chemical synthesis of various haptenic OSEs was demonstrated, and the genes encoding glycosylation pathway enzymes for the biosynthesis of GPLs were identified and characterized (8,12,19,21). However, genes responsible for serotype-specific glycosylation have yet to be analyzed for most of the serotypes.…”
mentioning
confidence: 99%